Challenges of Providing Humanitarian aid in Light of the Covid-19 Pandemic - Oualhi, Mokhtar (Journal of Legal Studies and Researches, 2022)
The repercussions of the Covid-19 pandemic caused a global imbalance at all levels, especially for fragile states that are already in crisis due to conflicts, natural disasters or climate change, and often depend on conflicts, natural disasters or climate change, and often depend on humanitarian aid to survive. This pandemic has spread quickly and effectively without the intervention of the international community, but the United Nations and between countries.